1970
DOI: 10.3126/jpn.v2i3.6027
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes in gallbladder mucosa associated with cholelithiasis

Abstract: Background: Gallstone is a very common gastrointestinal disorder. It is known to produce histopathological changes in the gallbladder. It is also one of the predisposing factors for the development of cancer of gallbladder. Materials and Methods: This was a retrospective study carried out in the Department of Histopathology, B and B Hospital during a period of 1 year from April 2010 to May 2011. The study included 396 cases of cholecystectomy specimens. Results: On gross examination, outer gallbladder surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 5 publications
4
13
1
3
Order By: Relevance
“…Cholesterolosis was found in 13% to 14% cholelithiasis specimens in two other studies. 11,18 There was no case of carcinoma in situ in the present study but one case of carcinoma was observed (0.53%). A similar percentage of gall bladder carcinoma was noted in asymptomatic cases in another study (0.57%).…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Cholesterolosis was found in 13% to 14% cholelithiasis specimens in two other studies. 11,18 There was no case of carcinoma in situ in the present study but one case of carcinoma was observed (0.53%). A similar percentage of gall bladder carcinoma was noted in asymptomatic cases in another study (0.57%).…”
Section: Discussioncontrasting
confidence: 53%
“…This is comparable to age and gall stone findings observed in few other studies. [8][9]11 41-50 years of life (5 th decade) is reported to witness peak incidence. 10 In our study we did not get any case that was younger than 20 years of age during the study period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In Nepal, histopathological examination of cholecystectomy specimens has become a routine practice. [6][7][8][9] Gallstone disease, porcelain gallbladder, and sclerosing cholangitis are the best known risk factors for gallbladder cancer apart from some nonmodifiable factors such as increasing age, ethnicity, female gender and family history or genetics. 9,10 Cholecystectomies performed with preoperative diagnosis of gallstone disease rarely results in a diagnosis of unexpected gallbladder cancer.…”
mentioning
confidence: 99%
“…Female Male et al, followed by congestion of the serosa in 30 cases (18.63%). [13][14][15] 106 cases presented with calculi (65.84%) with 55 cases (34.16%) being acalculus. Majority of the cases (31.06%) presented as multiple gall bladder calculi followed by single stones in 22.36% of cases.…”
Section: 78% (56)mentioning
confidence: 99%